2015
DOI: 10.1177/1203475415620396
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Year Retrospective Study of Basal Cell Carcinoma in a Canadian Dermatology Practice

Abstract: Our results show a preference of distinct BCC subtypes for certain anatomical locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
4
12
0
2
Order By: Relevance
“…Greek farmers with a sixfold increase in photodamaged skin have been recorded with an increased presentation of aggressive subtype BCC and less superficial BCC . A recent Canadian study also found nodular subtype BCC to be threefold more likely and aggressive BCC 2.4 times more likely on head and neck sites . We found a stronger head and neck site association with an increased shift towards a higher incidence of superficial combined with both nodular and aggressive BCC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Greek farmers with a sixfold increase in photodamaged skin have been recorded with an increased presentation of aggressive subtype BCC and less superficial BCC . A recent Canadian study also found nodular subtype BCC to be threefold more likely and aggressive BCC 2.4 times more likely on head and neck sites . We found a stronger head and neck site association with an increased shift towards a higher incidence of superficial combined with both nodular and aggressive BCC.…”
Section: Discussionsupporting
confidence: 67%
“…22 A recent Canadian study also found nodular subtype BCC to be threefold more likely and aggressive BCC 2.4 times more likely on head and neck sites. 23 We found a stronger head and neck site association with an increased shift towards a higher incidence of superficial combined with both nodular and aggressive BCC. This association may be due to longer duration and or more intense Australian solar exposure.…”
Section: Discussionmentioning
confidence: 52%
“…Most commonly nodular, then the superficial and infiltrative types of BCC are seen 1,16,17 . In our study, our cases had nodular (83.6%), superficial (9.6%), basosquamous (2.6%), and morpheaform (2.6%) subtypes of BCC similar to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…10 The number of necessary operations and the amount of incomplete excisions correlate with BCC size. 11…”
Section: Introductionmentioning
confidence: 99%